Crystal Structural of Phenanthroline and Thiocyanate Copper(II) Complex - Bi, Jian-Hong; Dong, Hua-Ze (Asian Journal of Chemistry, 2013)
A novel copper complex [Cu(phen)2(SCN)2] has been synthesized, with the 1,10-phenanthroline (phen) and the thiocyanate (SCN–) as ligands and characterized by IR spectra and single-crystal X-ray diffraction measurements. The crystal is orthorhombic, space group Pbcn with unit cell parameters: a =13.2449(15) Å, b = 10.0566(9) Å, c = 17.4257(16) Å, a = 90º, b = 90º, g = 90º, V = 2321.1(4) Å3, Z = 4, Mr = 540.11, Dc = 1.546 Mg/cm3, μ = 1.150 mm-1, F(000) =1100, T = 298(2) K, R = 0.0358, wR = 0.0803 for 8958 reflections with I > 2s(I). In the molecular structure unit, copper(II) cation is coordinated by six donor atoms.